Baubiologie : Kriterien und architektonische Gestaltung - Ece, Nurgül (Birkhäuser, 2018)
Health and environmental compatibility are the focus of society. The book shows how the built environment can be aesthetically modern and at the same time healthy and environmentally friendly. It bridges the gap between architecture as a creative task and building biology thinking. Building biology is the study of the holistic interactions of man and his built environment. It combines building culture with ecology and disciplines such as chemistry, biology, geology and psychology. On the model of the Institute for Building Biology + Sustainability (IBN) building biology criteria and approaches are explained in detail. Numerous other current projects illustrate how these have been implemented in a responsible, healthy and thus sustainable architecture.
Keywords: Architecture -- Human factors.; Architecture -- Environmental aspects.; Architecture, Modern -- 21st century -- Themes, motives.; Architecture -- Facteurs humains.; Architecture -- Aspect de l'environnement.; Architecture -- 21e siècle -- Thèmes, motifs.; Methods & Materials.; Design.; ARCHITECTURE.; Professional Practice.; Construction.; TECHNOLOGY & ENGINEERING.; Architecture -- Environmental aspects; Architecture -- Human factors; Architecture, Modern -- Themes, motives; 2000-2099; Electronic books.